2012
DOI: 10.1038/bjc.2012.383
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA profiling of diagnostic needle aspirates from patients with pancreatic cancer

Abstract: Background:A major challenge to the development of biomarkers for pancreatic cancer (PC) is the small amount of tissue obtained at the time of diagnosis. Single-gene analyses may not reliably predict biology of PC because of its complex molecular makeup. MicroRNA (miRNA) profiling may provide a more informative molecular interrogation of tumours. The primary objective of this study was to determine the feasibility of performing miRNA arrays and quantitative real-time PCR (qRT–PCR) from archival formalin-fixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(86 citation statements)
references
References 26 publications
3
78
0
4
Order By: Relevance
“…The two significantly upregulated miRNAs (miR-486-5p and miR-451) have not been well described in PDAC and deserve further investigation as possible oncogenic miRNAs. Regarding the validation of deregulated miRNAs, Ali et al should have considered validating miR-92a, as it was found to be significantly upregulated (log2-fold change +3.41) in PDAC on their microarray [1]. This miRNA is a member of the highly oncogenic polycistronic miR-17-92 cluster (aka oncomiR-1) [3] and has been shown to be upregulated in hepatocellular carcinoma [4] and a potential plasma and fecal biomarker for colorectal cancer [5].…”
Section: Validation Of Novel Pdac Mirnasmentioning
confidence: 92%
See 3 more Smart Citations
“…The two significantly upregulated miRNAs (miR-486-5p and miR-451) have not been well described in PDAC and deserve further investigation as possible oncogenic miRNAs. Regarding the validation of deregulated miRNAs, Ali et al should have considered validating miR-92a, as it was found to be significantly upregulated (log2-fold change +3.41) in PDAC on their microarray [1]. This miRNA is a member of the highly oncogenic polycistronic miR-17-92 cluster (aka oncomiR-1) [3] and has been shown to be upregulated in hepatocellular carcinoma [4] and a potential plasma and fecal biomarker for colorectal cancer [5].…”
Section: Validation Of Novel Pdac Mirnasmentioning
confidence: 92%
“…Furthermore, the study by Ali et al [1] is not the first to look at miRNAs in FFPE biopsies from PDAC patients. Although they used a different quantification technique, Preis et al [12] demonstrated that fluorescencebased in situ hybridization using locked nucleic acid-modified DNA probes against oncomiR-21 and miR-10b on FFPE sections of EUS-FNA samples could differentiate PDAC from normal pancreas (PDAC: n = 95; benign: n = 11).…”
Section: Expert Commentary and Five-year Viewmentioning
confidence: 98%
See 2 more Smart Citations
“…It is important to note that miR-486-5p has also been found to be downregulated in numerous other cancer types, including pancreatic cancer (34), gastric cancer (29), osteosarcoma (35), and lung cancer (23), however, the mechanism of miR-486-5p downregulation in those types of cancer, including HCC, is largely unknown. According to previous studies, miR-486-5p downregulation in HCC tissues could be highly accredited to its chromosomal location (8p11.21), which is one of the most typically occurring genomic deletion regions, containing potential tumor suppressor genes (29).…”
Section: A B Discussionmentioning
confidence: 99%